Early Childhood Creativity Festival Super Kids for a Great Indonesia: Through Batik Fashion Show, Puzzle Competition, and National Song Singing Competition at the North Sumatra State Museum - Putri Sari Ulfa Sembiring; Azizah Muthmainnah; Puri Telembanua (Outline Publisher, 2026)
The Community Service Program entitled